The influence of employee engagement, digital transformation and talent management on the performance of Mercure Hotel Jakarta Kota employees - Firmansyah, Rahmat; Napitupulu, Elfrida Viesta (Jurnal Ekonomi Perusahaan, 2024)
This research aims to analys the power of employee engagement, digital transformation, and talent management on employee performance. The population of this research is employees of the Mercure Jakarta Kota hotel. The sampling technique used is a completely filled of sample. So the total sample is 110 employees of the Mercure Jakarta Kota hotel. The research uses a quantitative approach with multiple linear regressions. The data that has been collected is calculated using the SPSS version 26 statistical program. The research results show that partially and simultaneously employee engagement, digital transformation, and talent management have a positive and important impact on the performance of Mercure Jakarta Kota hotel employees.